Spectroscopic investigations of divertor detachment in TCV. (August 2017) - Verhaegh, K.; Lipschultz, B.; Duval, B.P.; Harrison, J.R.; Reimerdes, H.; Theiler, C.; Labit, B.; Maurizio, R.; Marini, C.; Nespoli, F.; Sheikh, U.; Tsui, C.K.; et al.
Highlights: Advancements are made for extracting recombination rates from Balmer line spectra. Detached region stays near the target whilst the upstream density increases strongly. The recombination rate ( RV ) is low at the time of the particle flux (Γ) roll-over. After the Γ drop, at the highest core densities, RV reaches levels similar to Γ. Graphical abstract: Abstract: The aim of this work is to provide an understanding of detachment at TCV with emphasis on analysis of the Balmer line emission. A new Divertor Spectroscopy System has been developed for this purpose. Further development of Balmer line analysis techniques has allowed detailed information to be extracted from the three-body recombination contribution to the n = 7 Balmer line intensity. During density ramps, the plasma at the target detaches as inferred from a drop in ion current to the target. At the same time the Balmer 6 → 2 and 7 → 2 line emission near the target is dominated by recombination. As the core density increases further, the density and recombination rate are rising all along the outer leg to the x-point while remaining highest at the target. Even at the highest core densities accessed (Greenwald fraction 0.7) the peaks in recombination and density may have moved not more than a few cm poloidally away from the target which is different to other, higher density tokamaks, where both the peak in recombination and density continue to move towards the x-point as the core density is increased. The inferred magnitude of recombination is small compared to the target ion current at the time detachment (particle flux drop) starts at the target. However, recombination may be having more localized effects (to a flux tube) which we cannot discern at this time. Later, at the highest densities achieved, the total recombination does reach levels similar to the particle flux.